Aplicación de la propuesta didáctica basada en la lógica de la investigación científica para desarrollar el pensamiento crítico de los estudiantes del 2° año de la especialidad de historia y geografía en el curso de geografía física del Perú y del mundo de la facultad de educación y ciencias de la comunicación de la unt - Gutiérrez Alva, César Felipe (2014)
In traditional education, the process is primarily focused on the teacher, then the teacher was the supposed "owner of the truth" and transmitting knowledge through the implementation of teaching strategies; while the student played a passive role and merely memorize the tenets of "dixic magister". It follows that scientific thinking is fundamentally critical; problem and thoughtful not exist, because the characteristics of the teaching method focused mainly on the contents and underestimated the capacity building, skills and attitudes of students. Therefore, this research raises the following issue: To what extent the implementation of the educational proposal based on the logic of scientific research develops critical thinking of students of the 2nd year of the specialty of History and Geography in the course of Physical Geography of Peru and the World of Education and Faculty of Communication Sciences of the National University of Trujillo, during the 2012 academic year? The overall objective of this study was to determine to what extent the educational proposal based on the logic of scientific research develops critical thinking of students, assuming the hypothesis that the independent changeable significantly develops the dependent changeable. The design used to test the experimental hypothesis is not due to the existence of a single group, in which the pretest and post test was applied. The sample population consisted of 17 students of the 2nd year of the specialty of History and Geography enrolled in the course of Physical Geography of Peru and the world. The overall conclusion is that the application of the didactic proposal based on the logic of scientific research developed in 36.4% the optimal level of critical thinking skills of students.